Tri Hita Karana Oriented Problem Based Learning Improves Natural Science Learning Outcomes - Permatasari, Anak Agung; Widiana, I Wayan; Simamora, Alexander Hamonangan (Universitas Pendidikan Ganesha, 2020)
This research focused on the low learning outcomes of Natural Science students in class V.. The purpose of this study was to analyze the effect of the Tri Hita Karana oriented PBL model on the learning outcomes of the fifth grade Natural Science students. The sample in this study amounted to 56 students. In this study, data were collected using a test technique using an objective test instrument with multiple choice forms which had previously been analyzed for the quality of eligibility by testing the validity, reliability, distinguishing features, and level of difficulty. The data that has been obtained is then analyzed using t-test. Based on the results of the t-test analysis, T-count = 5.42, while the value of T-table at a significant level of 5% with degrees of freedom 28 + 28 - 2 = 54 is 1.67. Based on T-count = 5.42 > T-table = 1.67 then H0 is rejected. The results of the analysis prove that there are significant differences between the groups of students who are taught with the Tri Hita Karana oriented Problem Based Learning model with groups of students who are taught with conventional learning models. From the results of the t-test analysis and the average learning outcomes it can be concluded that The Tri Hita Karana oriented Problem Based Learning model has a positive effect on the Natural Science learning outcomes of Class V students. Therefore, the Tri Hita Karana oriented Problem Based Learning model is suitabel for dealing with low Natural Science learning outcome